2019
DOI: 10.1177/1352458519885107
|View full text |Cite
|
Sign up to set email alerts
|

Reduced neurite density in the brain and cervical spinal cord in relapsing–remitting multiple sclerosis: A NODDI study

Abstract: Background: Multiple sclerosis (MS) affects both brain and spinal cord. However, studies of the neuraxis with advanced magnetic resonance imaging (MRI) are rare because of long acquisition times. We investigated neurodegeneration in MS brain and cervical spinal cord using neurite orientation dispersion and density imaging (NODDI). Objective: The aim of this study was to investigate possible alterations, and their clinical relevance, in neurite morphology along the brain and cervical spinal cord of relapsing–re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 37 publications
(75 reference statements)
5
54
2
Order By: Relevance
“…For intraneurite volume fraction v in , our results point toward reduction in this metric in both lesions and NAWM in RRMS patients compared with healthy controls. Such reductions are consistent with previous findings (20,21,23,24), and may be indicative of diffuse axonal loss as well as secondary demyelination (19).…”
Section: Noddi Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…For intraneurite volume fraction v in , our results point toward reduction in this metric in both lesions and NAWM in RRMS patients compared with healthy controls. Such reductions are consistent with previous findings (20,21,23,24), and may be indicative of diffuse axonal loss as well as secondary demyelination (19).…”
Section: Noddi Resultssupporting
confidence: 92%
“…Abnormal DTI measures are seen in both lesions and so-called normal appearing white matter (NAWM) (featuring no obvious pathology on conventional MRI scanning) (16)(17)(18). There is evidence that validates the use of NODDI in MS (19)(20)(21), which suggest that while FA might be the most sensitive metric to detect abnormalities, NODDI metrics are able to detect areas of abnormality where FA is normal (22,23). Investigations into NODDI in MS have generally concluded that intra-neurite volume fraction decreases in both lesions and NAWM (20,21,24) whilst findings on orientation dispersion vary (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…These metrics, indeed, are complementary to each other and their spatial distributions overlap with all regions with reduced FA. In particular, a reduced NDI was detected only in cerebral regions in L-TLE patients, which is consistent with possible widespread WM alteration as shown in a previous work in epilepsy [25] and other neurological diseases [26], [27]. L-TLE patients also showed an increased ODI in brainstem and right cerebellum, indicating that here there might be a change in morphology of microstructure rather than cellular density [28].…”
Section: Discussionsupporting
confidence: 90%
“…13 We detail significant clinical findings reported in all published clinical studies in On-line Table 2. In summary, it was noted that when reaching a statistically significant difference, NDI/V ic values were always lower in lesions compared with normal-appearing WM, 12,[14][15][16] in normal-appearing WM compared with the normal WM of healthy controls (both in brains 14,16,17 and spinal cord 13,17 ), and in the spinal cord normal-appearing GM compared with the GM of healthy controls. 13 These results were consistent across patients with relapsing-remitting [12][13][14][15][16][17] or secondary-progressive MS. 12,16,17 However, thus far, only values of NDI measured in both the cortex 18 and the spinal cord 17 were found to be associated with clinical disability measured with the Expanded Disability Status Scale 19 in patients with both relapsing-remitting 17,18 and secondary-progressive 17,18 MS.…”
Section: Neurite Orientation Dispersion and Density Imagingmentioning
confidence: 87%